Perpetual Happiness The Ming Emperor Yongle - Tsai, Shih-shan Henry (Donald R. Ellegood International Publications, 2011)
The reign of Emperor Yongle, or "Perpetual Happiness," was one of the most dramatic and significant in Chinese history. It began with civil war and a bloody coup, saw the construction of the Forbidden City, the completion of the Grand Canal, consolidation of the imperial bureaucracy, and expansion of China's territory into Mongolia, Manchuria, and Vietnam. Beginning with an hour-by-hour account of one day in Yongle's court, Shih-shan Henry Tsai presents the multiple dimensions of the life of Yongle (Zhu Di, 1360-1424) in fascinating detail. Tsai examines the role of birth, education, and tradition in molding the emperor's personality and values, and paints a rich portrait of a man characterized by stark contrasts. Synthesizing primary and secondary source materials, he has crafted a colorful biography of the most renowned of the Ming emperors. The open access publication of this book was made possible by a grant from the James P. Geiss and Margaret Y. Hsu Foundation.